Using Web-Based Questionnaires and Obstetric Records to Assess General Health Characteristics Among Pregnant Women: A Validation Study - van Gelder, Marleen MHJ; Schouten, Naomi PE; Merkus, Peter JFM; Verhaak, Chris M; Roeleveld, Nel; Roukema, Jolt (JMIR Publications, 2015)
BackgroundSelf-reported medical history information is included in many studies. However, data on the validity of Web-based questionnaires assessing medical history are scarce. If proven to be valid, Web-based questionnaires may provide researchers with an efficient means to collect data on this parameter in large populations. ObjectiveThe aim of this study was to assess the validity of a Web-based questionnaire on chronic medical conditions, allergies, and blood pressure readings against obstetric records and data from general practitioners. MethodsSelf-reported questionnaire data were compared with obstetric records for 519 pregnant women participating in the Dutch PRegnancy and Infant DEvelopment (PRIDE) Study from July 2011 through November 2012. These women completed Web-based questionnaires around their first prenatal care visit and in gestational weeks 17 and 34. We calculated kappa statistics (κ) and the observed proportions of positive and negative agreement between the baseline questionnaire and obstetric records for chronic conditions and allergies. In case of inconsistencies between these 2 data sources, medical records from the woman's general practitioner were consulted as the reference standard. For systolic and diastolic blood pressure, intraclass correlation coefficients (ICCs) were calculated for multiple data points. ResultsAgreement between the baseline questionnaire and the obstetric record was substantial (κ=.61) for any chronic condition and moderate for any allergy (κ=.51). For specific conditions, we found high observed proportions of negative agreement (range 0.88-1.00) and on average moderate observed proportions of positive agreement with a wide range (range 0.19-0.90). Using the reference standard, the sensitivity of the Web-based questionnaire for chronic conditions and allergies was comparable to or even better than the sensitivity of the obstetric records, in particular for migraine (0.90 vs 0.40, P=.02), asthma (0.86 vs 0.61, P=.04), inhalation allergies (0.92 vs 0.74, P=.003), hay fever (0.90 vs 0.64, P=.001), and allergies to animals (0.89 vs 0.53, P=.01). However, some overreporting of allergies was observed in the questionnaire and for some nonsomatic conditions sensitivity of both measurement instruments was low. The ICCs for blood pressure readings ranged between 0.72 and 0.92 with very small mean differences between the 2 methods of data collection. ConclusionsWeb-based questionnaires can be used to validly collect data on many chronic disorders, allergies, and blood pressure readings among pregnant women.